Firestorm - Johansen, Iris (New York : Bantam Books, 2005)
Arson specialist Kerry Murphy solves crimes with the help of her dog Sam, but behind her reputation as a fire detective, she hides a terrifying secret that explains her success more thoroughly than her hard work and dedication.
National College of Business and Arts
Keywords: Arson investigation -- Fiction; Psychological fiction